Brain arteriovenous malformation treatment with transvenous endovascular technique after transarterial technique failure - Gonçalves, Daniel Buzaglo; Oliveira, Louise Makarem; Salles, Moisés Buzaglo; Cabral, Lucas de Cristo Rojas; Santos, Maria Izabel Andrade dos; Takatani, Vitória Miki Pang; Coutinho, Gabriela Campos da Silva; Takatani, Massanobu; Peres, Carlos Michel Albuquerque; Amorim, Robson Luís Oliveira de (Brazilian Journal of Case Reports, 2021)
Arteriovenous malformations (AVMs) are unnatural connections in the vascular system. The treatment strategies are dictated by the angioarchitecture, location and presentation of AVMs. The present study sought to report a case report of a 35-year-old female patient diagnosed with a brain AVM and submitted to a transvenous AVM embolization, located at the corpus callosum's splenium, after a previous transarterial embolization failure. As a therapeutic approach, the patient was submitted to transarterial embolization. However, the procedure was performed too proximally in the arteries, which resulted in the total AVM persistency. The patient was submitted to angiographic control until complete AVM occlusion.